Post Burn Microstomia: Challenges and Comprehensive Management - Mohd. Altaf Mir; Sakshita Pal; Sarabjot Singh Anant; Rahul Kaushik; Ashwini Tiwari (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
This book chapter explores the obstacles faced by healthcare professionals in the management of patients suffering from microstomia, a condition resulting from orofacial, and neck burns with subsequent contractures. Postburn microstomia poses dual challenges for both the anesthesiologist and the plastic surgeon due to the severe restriction in oral opening, making airway management and surgical intervention complex tasks. To address these challenges, this chapter delves into the innovative use of fiberoptic nasal intubation techniques, which offer a unique solution for navigating the challenging anatomy and ensuring patient safety during intubation. Furthermore, it explores the surgical aspect of managing microstomia through bilateral oral commissuroplasty, a reconstructive procedure aimed at not only restoring oral function but also achieving aesthetically pleasing results. This comprehensive approach underscores the collaborative efforts of anesthesiologists and plastic surgeons in managing patients with severe microstomia, emphasizing the importance of both functional and aesthetic considerations, ultimately improving patient outcomes and quality of life.